Environmental Law and Residential Exclusion: Protecting the Environment or Preserving Neighborhood Status Quo? - Patton, Dorothy E. (Columbia Journal of Environmental Law, 2019)
There is a growing practice whereby environmental protection principles and the impact statement provisions of the National Environmental Policy Act' (NEPA) are utilized in efforts to bar housing or other facilities provided for unwanted social groups. This seeming adjunct to the environmental protection movement creates lawsuits in which environmental claims and defenses are offered to justify exclusionary purposes or effects. As a result, these cases present questions as to whether a legal strategy which relies on environmental law to justify exclusionary practices is an appro- priate use of environmental protection concepts. This Comment will examine the variable meanings of the terms "environment" and "people pollution" and the use of these concepts in the service of exclusionary objectives in cases decided under local laws and NEPA.